Prevalence, clinical characteristics and outcome of COVID-19 infection among healthcare workers: a retrospective analysis in a single northwest Malaysia specialist centre - A, Ainur Iznita; M, Irma Liyana; J, Nurul Faizah; A, Ahmad Zulhafizi (Penerbit Universiti Kebangsaan Malaysia, 2023)
Healthcare workers (HCWs) are most susceptible to COVID-19 because they are constantly exposed to the source. This study aimed to determine the prevalence, clinical characteristics, and outcome of healthcare workers (HCWs) with positive COVID-19 in a single institution in northwest Malaysia. Data log of HCWs diagnosed with positive COVID-19 with real-time reverse transcription-polymerase chain reaction (RT-PCR) between 1st January 2021 and 31st December 2021 in Hospital Tuanku Fauziah, Perlis, Malaysia was retrospectively analysed. A total of 198 HCWs were included. Majority were female (72.2%), mean age of 39.9 + 6.55 years, Malay (96%), nurses (46%), without co-morbidities (92.4%) and had completed two doses of COVID-19 vaccination (97%). A total of 115 HCWs contracted the infection from the community, whereas 65 HCWs may be infected from the workplace. Most of the staff were symptomatic (84.3%). Fever (49%), sore throat (40.4%), cough (33.8%) and runny nose/nasal congestion (22.2%) are the most prominent symptoms. A total of 82.8% of HCWs were diagnosed with stage 2 COVID-19. The median length of infection to occur was approximately 5 months after two doses of vaccination. Majority were manageable at home during diagnosis (76.2%), with no deaths were recorded. Symptomatic HCWs had significantly longer interval of COVID-19 vaccination-to-infection period (p<0.001). The HCWs diagnosed with stage two COVID-19 had significantly longer interval of COVID-19 vaccination-to-infection as compared to stage one COVID-19 (p=0.012). Periodic evaluation of COVID-19 infection among HCWs is essential for the development of effective mitigation strategies for optimal pandemic control as well as for HCWs protection during the endemic phase.